The DETERMINAN PENGUNGKAPAN LAPORAN KEBERLANJUTAN DENGAN TATA KELOLA PERUSAHAAN YANG BAIK SEBAGAI VARIABEL MODERASI - Sulaksono, Anggi; Darminto, Dwi Prastowo; Ahmar, Nurmala (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The purpose of this study is to analyze the effect of Determinants of Disclosure of Sustainability Reports as measured by Financial Performance and Company Characteristics with the Board of Commissioners as a Moderating Variable. The population used in this study are all non-financial companies listed on the SRIKEHATI Index for the 2019-2022 period. The data used is secondary data for 19 companies obtained from the Company's website and the Indonesian Stock Exchange's website. Methods of data analysis using descriptive analysis and analysis with the SEM-PLS (Structural Equation Modelling - Partial Least Square) method. The results of this study indicate that the ownership variable has an effect on the disclosure of sustainability reports and the variables of profitability, liquidity, company size, company age have no effect on the disclosure of sustainability reports. The role of the Board of Commissioners is proven to moderate the influence of the Profitability variable on the disclosure of sustainability reports.